miR-221/222 overexpession in human glioblastoma increases invasiveness by targeting the protein phosphate PTPμ - Quintavalle, C (Oncogene, 2011)
Glioblastoma is the most frequent brain tumor in adults and is the most lethal form of human cancer. Despite the improvements in treatments, survival of patients remains poor. In order to identify microRNAs (miRs) involved in glioma tumorigenesis, we evaluated, by a miRarray, differential expression of miRs in the tumorigenic glioma LN-18, LN-229 and U87MG cells compared with the non-tumorigenic T98G cells. Among different miRs we focused our attention on miR-221 and -222. We demonstrated the presence of a binding site for these two miRs in the 3′ untranslated region of the protein tyrosine phosphatase μ (PTPμ). Previous studies indicated that PTPμ suppresses cell migration and is downregulated in glioblastoma. Significantly, we found that miR-221 and -222 over-expression induced a downregulation of PTPμ as analyzed by both western blot and real-time PCR. Furthermore, miR-222 and -221 induced an increase in cell migration and growth in soft agar in glioma cells. Interestingly, the re-expression of PTPμ gene was able to revert the miR-222 and -221 effects on cell migration. Furthermore, we found an inverse correlation between miR-221 and -222 and PTPμ in human glioma cancer samples. In conclusion, our results suggest that miR-221 and -222 regulate glioma tumorigenesis at least in part through the control of PTPμ protein expression.